Mechanical ventilation in snake envenomation of dogs and cats - Morris, Cameron A. D.; Donaldson, Rebekah E. (Frontiers in Veterinary Science, 2023)
Envenomation by snakes in Elapidae and Viperidae families have been associated with respiratory failure in dogs and cats. Mechanical ventilation may be required for hypoventilation due to neuromuscular paralysis or hypoxemia due to pulmonary hemorrhage or aspiration pneumonia. Median incidence of dogs and cats with snake envenomation that require mechanical ventilation is 13% (0.06 – 40%). Standard treatment of snake envenomation in dogs and cats includes prompt administration of appropriate antivenom and management of envenomation complications such as coagulopathy, rhabdomyolysis and acute kidney injury. When mechanical ventilation is required, overall prognosis is good with appropriate treatment. Standard anesthetic protocols and mechanical ventilator settings are generally appropriate, with lung protective ventilation strategies typically reserved for patients with pulmonary disease. Median survival to discharge for cats and dogs with elapid envenomation is 72% (76 – 84%) with 33 hours (19.5 – 58 hours) median duration of mechanical ventilation and 140 hours (84 – 196 hours) median hospitalization. This article reviews indications for mechanical ventilation in cats and dogs with snake envenomation, and discusses ventilator settings, anesthetic and nursing considerations, complications and outcomes specific to this disease.